Histological analysis of the insertion of the superior lateral pterigoid muscle fascicle at articular disk - Alvarado Menacho, Sergio Francisco (2012)
The inclusion of the fascicle higher external pterygoid muscle (Lateral Pterigoid) disk articulate occurs from the middle third of the central region and contributes to the displacement of the disc and its alteration help discal displacement. On the insertion, there are differences of opinion; some consider that only a small portion of fiber is inserted into the anterior capsule and thus directly and indirectly to the disk; other researchers point out that it is directly inserted the disk and the condyle or only on the anterior edge of the capsule and the disc. The objective of the study was a histological analysis of the insertion of this muscle to differentiate the type of fibres that reach the disk articulate (proportion of collagen fibers and muscle fibers) and determine the type of union between the muscle and the disc articulate. The sample of this study of transverse and exploratory type, was constituted by prepared diesiseis anatomical joint, temporomandibular, proceding for his histological reading with stains Hematoxylin and Eosin, Van Guiesson and Mallory, having found that the largest proportion of fibers reaching insert disk articulate are collagen and type of Union between the muscle and the disc articulate is sandwiched in a longitudinal way.